Issues and Challenges of Ethnicity in Nepal: Arguments Against Primordial Conception - Kaini, Tika Raj; Dhakal, Naba Raj (NUTA Journal, 2024)
This article seeks to invalidate the primordial conception, manifested in academia and activism in Nepal arguing that ethnic identities are not fixed and given rather they are contingent and fluid. The fluidity takes the shape during the interaction and communication of different ethnic groups and communities. The continual intergroup interaction contributes to construction of mix-identities. The process of making mixed identities reject the scholarly view that ethnicity is biological. Biological traits of ethnicity further lose its shape in the process of migration that forms the identity in different way. Notwithstanding the reality of loss of territorial inhabitation of specific ethnic groups as it were in the past, ethnic scholars and activists voiced the idea of ethnic federalization which was already invalidated by the constitution of 2015 AD. Stating that, our argument is not against the inclusion, representation and dignity of the marginalized groups in Nepal. The issue of language and proper representation of the ethnic groups are to be addressed and include diversity of the groups in mainstream. In contrast, the issue of right of ethnic self-determination in the back of ethnic federalization is not feasible because of the existence of diverse ethnic and non-ethnic groups and also their cohabitation throughout Nepal. This article also seeks to discuss the challenges ethnic movement experiences. The party affiliate and indoctrinated movement has lost its independent character on one side and the failure of ethnic based political parties demanding on ethnic federalization explicitly and implicitly on the other proves that right of self-determination in invalidated. This study is purely qualitative. To argue against the spirit of primordial conception, Content analysis has been chosen as the method.